Compression and impact characterization of helical and slotted cylinder springs - Razooqi, Ahmed Ibrahim; Ameen, Hani Aziz; Mashloosh, Kadhim Mijbel (International Journal of Engineering and Technology, 2014)
Helical and slotted cylinder springs are indispensable elements in mechanical engineering. This paper investigates helical and slotted cylinder springs subjected to axial loads under static and dynamic conditions. The objective is to determine the stiffness of a circular cross-section helical coil compression spring and slotted cylinder springs with five sizes and dynamic characteristics. A theoretical and finite element models are developed and presented in order to describe the various steps undertaken to calculate the spring’s stiffnesses. Five cases of the spring’s geometric are presented. A finite element model was generated using ANSYS software and the stiffness matrix evaluated by applying a load along the spring’s axis, then calculating the corresponding changes in deformation. The stiffness is obtained by solving the changes of load and deformation. The natural frequencies, mode shapes and transient response of springs are also determined. Finally, a comparison of the stiffnesses are obtained using the theoretical methods and those obtained from the finite element analysis were made and good agreement are evident and it can be found that the stiffness of spring for the slotted cylinder spring is much larger than that for helical spring and the stiffness for slotted cylinder spring increases with the number of slots per section. Natural frequencies, mode shape and transient response of helical spring and slotted cylinder spring have been represented in ANSYS software and results have been compared and it found that the natural frequency has also increased in the same proportion of stiffness because the natural frequency is directly proportional to the stiffness for all the cases that have been studied. Keywords: ANSYS, Finite Element Analysis, Helical Spring, Slotted Cylinder Spring, Stiffness.